Influence Liquidity, Ownership Managerial, and Free Cash Flow To Policy Debt With Asset Structure As Variables Moderation in the Trade, Services and Investment Sectors Registered on the IDX for the 2021-2023 Period - Mardiyah, Nur; Amna, Luke Suciyati; Aminah, Aminah (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
Study This is study quantitative aiming? For see How contribution liquidity , ownership managerial , and free cash flow that has an impact to policy debt with asset structure as variable moderation.Data used? For study This is report finance annual sector trade, services and investment listed on the Indonesia Stock Exchange. The purposive sampling method was used For gather sample research consisting of 33 samples. The results of the research This show that (1) liquidity influential negative No significant to policy debt (2) ownership managerial influential positive significant to policy debt (3) free cash flow influential negative significant to policy debt (4) asset structure as variable moderation capable strengthen influence variable liquidity, ownership managerial, free cash flow against policy debt.